Inter-laboratory mass spectrometry dataset based on passive sampling of drinking water for non-target analysis - Bastian Schulze (Nature Portfolio, 2021)
Measurement(s) chemical • drinking water Technology Type(s) high resolution mass spectrometry • non-target analysis • Interlaboratory Factor Type(s) method Sample Characteristic - Environment laboratory environment Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.15028665